Association Between Anteromedial Portal Versus Tibial Tunnel Drilling and Meniscal Reoperation Risk Following Anterior Cruciate Ligament Reconstruction: A Cohort Study. Issue 9 (July 2022) - Davis, Brent R.; Chang, Richard N.; Prentice, Heather A.; Tejwani, Samir G.; Morris, Andrew J.; Maletis, Gregory B.
Background: Anterior cruciate ligament reconstruction (ACLR) provides functional stability to an injured knee. While multiple techniques can be used to drill the femoral tunnel during ACLR, a single technique has yet to be proven as clinically superior. One marker of postoperative functional stability is subsequent meniscal tears; a lower risk of subsequent meniscal surgery could be expected with improved knee stability. Purpose: To determine if there is a meniscal protective effect when using an anteromedial portal (AMP) femoral tunnel drilling technique versus transtibial (TT) drilling. Study Design: Cohort study; Level of evidence, 2. Methods: Data from Kaiser Permanente's ACLR registry were used to identify patients who had a primary isolated ACLR between 2009 and 2018; those with previous surgery in the index knee and meniscal pathology at the time of ACLR were excluded. The exposure of interest was TT (n = 2711) versus AMP (n = 5172) drilling. Multivariable Cox proportional hazard regression was used to evaluate the risk of a subsequent ipsilateral meniscal reoperation with adjustment for age, sex, femoral fixation, and graft choice. We observed a shift in surgeon practice from the TT to AMP over the study time frame; therefore, the relationship between technique and surgeon experience on meniscal reoperation was evaluated using an interaction term in the model. Results: At the 9-year follow-up, the crude cumulative meniscal reoperation probability for AMP procedures was 7.76%, while for TT it was 5.88%. After adjustment for covariates, we observed a higher risk for meniscal reoperation with AMP compared with TT (hazard ratio [HR], 1.53; 95% CI, 1.05-2.23). When stratifying by surgeon experience, this adverse association was observed for patients who had their procedure performed by surgeons with less AMP experience (no previous AMP ACLR: HR, 1.26; 95% CI, 0.84-1.91) while a protective association was observed for patients who had their procedure with more experienced surgeons (40 previous AMP ACLRs: HR, 0.34; 95% CI, 0.13-0.92). Conclusion: Drilling the femoral tunnel via the AMP was associated with a higher risk of subsequent meniscal surgery compared with TT drilling. However, when AMP drilling was used by surgeons experienced with the technique, a meniscal protective effect was observed.